Comparison of the antioxidant effect and phenolic profile of two Crataegus extracts - Hilal Bardakci; Kevser Ozdemir; Timur Hakan Barak; Elif Begum Yildirim; Feyza Sebnem Gorur (Medicine Science, 2020)
This study was designed to evaluate the phenolic profiles and antioxidant potentials of two commercial Crataegus monogyna Jacq samples, which are commonly used for various medicinal purposes. One of the samples supplied from the pharmacy and the other sample supplied from the herbalist shop. To analyze phenolic contents of samples Total Phenolic Content, Total Flavonoid Content and Total Phenolic Acid Content Assays were carried out. Further hyperoside contents, which is one of the major component of the genus, were determined by HPTLC method. Antioxidant bioactivities were established by using CUPRAC (Cupric Reducing Antioxidant Capacity), FRAP (Ferric Reducing Antioxidant Power), DPPH radical scavenging activity and TOAC (Total Antioxidant Capacity) methods. The comparison between two samples showed that the pharmacy product has higher phenolic ingredients than herbalist shop, consequently, has higher antioxidant bioactivity. [Med-Science 2020; 9(2.000): 323-6]